Equilibrium involuntary unemployment under oligempory - Leo Kaas; Paul Madden (Institute for Advanced Studies (IHS), 1999)
We show that equilibrium involuntary unemployment emerges in a multi-stage game model where all market power resides with firms, on both the labour and the output market. Firms decide wages, employment, output and prices, and under constant returns there exists a continuum of subgame perfect equilibria involving unemployment. A firm does not undercut the equilibrium wage since then high wage firms would attract its workers, thus forcing the low wage firm out of both markets. Full employment equilibria may also exist, but only the involuntary unemployment equilibria are robust to decreasing returns.
Keywords: D43; E24; 330; involuntary unemployment; multi-stage game; imperfect competition; Arbeitslosigkeit; Gleichgewichtstheorie; Oligopol; Theorie; Unfreiwillige Arbeitslosigkeit